P536 Minimally invasive gasless technique for ileocolic resection using an existing McBurney incision. (16th January 2018) - Fazzolari, L; Bagaglini, G; D'Ugo, S; Sensi, B; Di Giorgio, A; Sica, G
Abstract: Background: Laparoscopic ileocolic (IC) resection is considered the preferred surgical approach for patients with ileocaecal Crohn's disease (CD) requiring surgery. In 20% of cases, patients will present having had a previous appendectomy. The objective of this study was to prove safety and feasibility of using a previous Mc Burney incision to perform a minimally invasive IC resection for complicated CD. Methods: All consecutive patients who have had an open appendectomy through a Mc Burney incision and scheduled for IC resection for CD (from January 2016 to October 2017) at our Institution, were included in the study. Pre-operative and intraoperative setting was as for standard laparoscopic IC resection. Skin incision was performed at the exact point of the Mc Burney scar; the small size (2.5–6 cm) Alexis O wound protector/retractor (Applied Medical, 22872 Avenida Empresa, Rancho Santa Margarita, CA 92688, USA) was employed to protect and retract the wound margins and to allow a quick laparoscopy at the end of the procedure. The use of analgesics, PONV and the capability of accomplish to our protocol of ERAS for laparoscopic IC resection was evaluated. Results: Patients included were six males and three females. Median age was 40 years; BMI was within normal range. Three patients had penetrating disease with multiple fistulas, in two cases with the sigmoid colon. Four patients had stenosis of the terminal ileum. Two patients had both. It was possible to undertake the required operation in all nine patients without any need to "convert" to laparoscopy. Mean operative time was 100 min. No intraoperative complication was detected in this small series. At the final "exploratory laparoscopy" no abnormal findings were detected. The mean size of the surgical incision was 4 cm, shorter than the existing Mc Burney scar. There was one postoperative complication, with wound infection treated with antibiotics. All patients but one was compliant to our ERAS protocol. Mean postoperative hospital stay was 4 days (range 3–6). Conclusions: The Minimally invasive gasless technique through an existing Mc Burney incision is safe and feasible to perform IC resection for complicated CD. Higher BMI, fistula and involvement of sigmoid were not limiting factors. The incision required is very limited, shorter than the existing scar. The use of the Alexis O wound protector is very useful to access the abdominal cavity and it is handy in case of conversion to laparoscopy. Further studies to explore this minimally invasive IC resection may be indicated to evaluate possible advantages, such as time and cost savings, as well as reduction of patient's trauma.